Innovation in the Artificial Intelligence sector: An exploratory study of the structure of co-inventor networks - Lantz, Jean-Sébastien; Lacaze, Delphine; Braune, Eric; Sahut, Jean-Michel (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2024)
Through an analysis of the global co-inventor networks of the 30 most innovative companies in Artificial Intelligence (AI), this research provides three key contributions: 1) the two dimensions of co-inventor networks: “encapsulation of information and knowledge,” concerning the overall network structure, and “accessibility to information and knowledge,” related to the inventor’s position within the network; 2) geographic location influences the structure of these networks; 3) the most innovative companies strategically choose between these dimensions in a global competitive context. These findings reignite the debate on the importance of connectivity and central positioning versus brokerage to achieve high levels of patent production in AI.